Development of teaching competencies through the professional teaching practice - Lopez Garcia, Adriana Paola; Mancipe Moreno, Nestor Yesid; Sandoval Sanchez, Monica Paola (Corporación Universitaria Minuto de Dios, 2015)
This research reports the findings of a systematization of experiences whose main purpose was to identify the competencies developed by student teachers during their professional teaching practice. In 2014, students from the Bachelor Program in English Language Teaching at Uniminuto University worked as student teachers in Luigi Pirandello and Instituto Técnico Distrital Republica de Guatemala Schools where they had to deal with different situations in the classroom. Teaching journals, semi-structured interviews, and questionnaires, were used as data collection instruments. Findings suggest that context (public or private) is a determining factor when it comes to the development of teaching competencies.
Keywords: Systematization of Experiences; Teacher Competencies; Teacher Training and Teacher Development; PERSONAL DOCENTE - INVESTIGACIONES; PEDAGOGÍA - PRACTICA PROFESIONAL; FORMACIÓN PROFESIONAL DE MAESTROS